IDENTIFIKASI HAZARD DAN PERANCANGAN SISTEM INFORMASI KESELAMATAN DAN KESEHATAN KERJA DI UNIT AMONIAK (Studi Kasus : PT. PETROKIMIA GRESIK) - Eko Nurmianto (Prodi Teknik Industri Universitas Muhammadiyah Gresik, 2018)
Safety ergonomic is compulsory thing to be applied in every company to guarantee workers safety. To see how far safety ergonomic implemented, instead doing SMK3 audit, risk assessment approach method is other exemplary way by identifying the existing hazards and to measure how concern is the company in safety ergonomic subject. PT. Petrokimia Gresik is one of chemical company known as fertilizer producer which had outstanding acknowledgement in safety ergonomic subject, one of them is zero accident award. The definition of zero accident here is the company has minimum level of high risk accident, not with the understanding that the company has no accident at all. In despite of that, risk assessment method is still needed in order to monitoring action. Risk assessment is performed to produce a data that can expose areas where only a high hazards level exist, kind of hazards, and how to prevent and control the hazards. During this process, results are stored only to make an evaluation of the company, in thisproblem analysis, researcher will design an information system that will be a media repository and facilitate the users to know if there are hazards in a work unit